JILBAB AS THE LEGAL LANGUAGE AND STANDARD OF PERSONAL CONDUCT IN SOCIETY - Rohadi Rohadi (Universitas Muhammadiyah Ponorogo, 2020)
Language is a tool or instrument in reflecting an idea, thoughts, ideas, desires andwishes from one person to another person. It cannot be imagined how human life wouldbecome without language. Surely we will not be able to develop and pass down theculture or noble values of our nation's culture to the next generation, as is the case withanimal life. Animals do not have the ability to speak, so their ability to build civilizationis also lost. In addition, without the ability of human language cannot thinksystematically and orderly.The hijab is one of the legal language that applies and reflects the culture or behaviorthat applies in society. But the meaning, along with the passage of time feels a changein meaning. This is the entry point for the author to elaborate the veil as a legallanguage and standards of personal behavior in Indonesian society.How is the concept of hijab in legal language that is often used by Muslim women orgirls under the shadow of the terrorist and fundamentalist Islamic issues by certaingroups or those who do not like it and the hijab as a syar'i obligation for Muslimwomen so that it sticks as a symbol (character) for good Muslim women.